A 2‐year review of publicly funded cell‐free DNA screening in Ontario: utilization and adherence to funding criteria. (21st November 2019) - Bellai‐Dussault, Kara; Meng, Lynn; Huang, Tianhua; Reszel, Jessica; Walker, Mark; Lanes, Andrea; Okun, Nan; Armour, Christine; Dougan, Shelley
Abstract: Objective: Ontario offers a publicly funded modified contingent model of prenatal screening for aneuploidy in which cell‐free DNA (cfDNA) screening is covered for pregnancies at higher risk of fetal aneuploidy. The objective of this study was to review utilization of provincially funded cfDNA screening and adherence to the criteria laid out in Ontario prenatal screening guidelines. Methods: This was a descriptive cohort study using data collected by Ontario's prescribed maternal and child registry. The study population included all pregnant individuals who received cfDNA screening from January 2016 to December 2017. Results: The most common criteria for provincially funded cfDNA screening were advanced maternal age ≥40 years (37.7%), positive multiple marker screen (34.1%), modifying risk factors such as ultrasound soft markers (7.1%), and previous aneuploidy (5.5%). The audit demonstrated that 2.9% of funded cfDNA screens tests did not meet funding criteria, and that 11.4% of self‐paid cfDNA screens could have been publicly funded. Conclusion: Reviewing and auditing the application of criteria for funded cfDNA screening using prescribed registry data allows an opportunity to identify areas where targeted education may improve adherence to standardized screening protocols, and provides a basis for reassessment of the funding model. Abstract : What's already known about this topic? CfDNA screening is included in many jurisdictions' prenatal screening algorithm. Some jurisdictions have adopted a contingent model where cfDNA screening is offered in pregnancies at increased risk of aneuploidy, whilst others have adopted a universal approach, offering cfDNA screening in all pregnancies. What does this study add? This study provides insight into how eligibility criteria for publicly funded cfDNA screening are being applied in Ontario's modified contingent model and where system improvements could be made. This study provides data on trends in utilization of cfDNA screening in Ontario and the application of funding criteria, which can be considered by other local and international jurisdictions to inform the planning and implementation of funded cfDNA screening in their setting.